Programa educativo de diarios interactivos para la mejora de producción de textos en inglés en estudiantes de cuarto grado de secundaria en la Institución Educativa Primaria Secundaria De Menores 60115 Almirante Miguel Grau Seminario, Padre Cocha 2021 - Saavedra Pipa, Katherine Fiorella (2023)
The primary aim of this research was to evaluate the effectiveness of an interactive journal-based training program for learners in their fourth year at Almirante Miguel Grau Seminario Secondary School, Padrecocha 2021, in enhancing their English writing skills. The research type was evaluative employing a field study, contemporary transectional, univariate, and quasi-experimental designs with pre-test, post-test and control group. The research population consisted of 270 male and female students, with a non-probabilistic sample of 52, divided into two groups: 4th B the experimental group with 26, and 4th C the control group with 26 students. Post-test results revealed that the experimental group performed better than the control group, with a higher mean score (15,22 >10,11). Similar results were evident for its dimensions. In conclusion, the interactive diary-based learner-training program significantly enhanced learners’ writing skills, as evidenced by the p-value was 0.000 < Ժ=0.05, and the working hypothesis was accepted.